Effect of Resistance Training on Serum Level of C-Reactive Protein (CRP) and Fibrinogen in Male Addicts - abbas saremi; hassan khalaji; sohrab momeni (Drug Control Headquarters, Research and Education Office, 2016)
Objective: Addiction to narcotic drugs is associated with cardiovascular diseases; and increased levels of biomarkers, such as C-reactive protein and fibrinogen are independently correlated with the risk of cardiovascular diseases. Therefore, this study aimed to investigate the effects of 8 weeks of resistance training on C-reactive protein and fibrinogen levels in drug addicted men. Method: In this quasi-experimental study with pretest-posttest, the number of 30 male addicts was randomly divided into resistance training group (n = 15) and non-sports control group (n = 15). Then, resistance training was conducted within two months, four days a week, and 50 to 60 minutes a day. The serum levels of C-reactive protein, fibrinogen, body compositions, and metabolic parameters were evaluated before and after the training period. Results: After the passage of 8 weeks of resistance training, skeletal muscle strength significantly increased (P < .05). At the same time, levels of C-reactive protein and fibrinogen significantly decreased in response to resistance training (P < .05). Conclusion: Short-term resistance training program improves muscle mass and strength in the male addicts after drug abstinence and this improvement is associated with reduced levels of C-reactive protein and fibrinogen.